Instability of the tetrathionate respiratory chain of Citrobacter freundii - Novotný, C (Folia microbiologica, 1978)
The formate--tetrathionate reductase redox pathway of Citrobacter freundii is associated with the cytoplasmic membrane fraction. A high concentration of phosphate in the buffer used for cell disintegration assists in the preparing of membrane particles capable of efficient tetrathionate respiration. A part of this effect at least may be attributed to the high ionic strength of the buffer.
Keywords: Thiosulfates; formiáty; thiosírany; oxidace-redukce; Cell Fractionation; Formates; frakcionace buněk; Citrobacter; Tetrathionic Acid; buněčná membrána; Oxidation-Reduction; Cell Membrane; kyselina tetrathionová; Oxidoreductases; oxidoreduktasy